Genotype-environment interaction for post-weaning traits in Nellore beef cattle - Guidolin, D. G. F. [UNESP]; Buzanskas, M. E. [UNESP]; Ramos, S. B. [UNESP]; Venturini, G. C. [UNESP]; Lobo, R. B.; Paz, C. C. P.; Munari, D. P. [UNESP]; Oliveira, J. A. [UNESP] (CSIRO Publishing, 2012)
Identification of genotype-environment interaction in beef cattle may help the artificial selection process and increase the efficiency of genetic evaluation on sires submitted to different environments. Post-weaning traits are economically important and are more influenced by the effects of genotype-environment interactions than pre-weaning traits. Thus, the aim of this study was to investigate whether this interaction has any effect on bodyweight at 365, 450, and 550 days of age in Nellore cattle reared in Brazil. Analyses considered the states of Goias, Mato Grosso, Mato Grosso do Sul, Minas Gerais, Para, and São Paulo. Genetic parameters were estimated for each trait, per state, using the restricted maximum likelihood method, in two-trait analysis under an animal model. Genetic correlations regarding the same trait in two different states were used to evaluate the effect of the genotype-environment interaction on the traits studied. Genetic correlation estimates smaller than 0.80 between observations for the same trait in different states were taken to be indicative of genotype-environment interaction. It was observed that there is evidence of genotype-environment interaction in some of the states studied, and they tend to increase when the weight measurements are made at later ages. From this, it was concluded that selection conducted using data from one state might be different from selection based on data from another state. Summaries of bulls that consider different environments could contribute greatly to the genetic improvement of livestock.